The Relationship between Critical thinking and Achievement Motivation among Fifth Grade Pupils: A Field Study in AlKadmous City - نصور, رغداء; ابو شاهين, مصطفى شاهين (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research aimed to identify the level of critical thinking and achievement motivation among fifth grade pupils in AlKadmous city, and to examine the relationship between them, beside testing gender differences. Hence, the researcher designed a critical thinking test, based upon RED model, and adopted an achievement motivation scale. Then, he administered them on a (140) pupils random sample, from first cycle government schools. Results showed an average level of critical thinking, and a high level of achievement motivation, among fifth grade pupils, with no differences between boys and girls at both. Results, also, reveals a significant positive relationship, at moderate level, between critical thinking and achievement motivation. Many recommendations were suggested.